2006
DOI: 10.1001/archpedi.160.12.1285
|View full text |Cite
|
Sign up to set email alerts
|

The Extent to Which Tobacco Marketing and Tobacco Use in Films Contribute to Children's Use of Tobacco

Abstract: Pro-tobacco marketing and media stimulate tobacco use among youth. A ban on all tobacco promotions is warranted to protect children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
103
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(113 citation statements)
references
References 116 publications
(97 reference statements)
6
103
2
1
Order By: Relevance
“…Numerous prosmoking messages reach young children through current and classic media and researchers have found a dose-response relationship between such exposure and smoking. 7 A rating system that alerts parents and guardians to this "mature content" could help reduce youth exposure. 30 In addition to public health and policy advocates, this study has implications for pediatric health professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous prosmoking messages reach young children through current and classic media and researchers have found a dose-response relationship between such exposure and smoking. 7 A rating system that alerts parents and guardians to this "mature content" could help reduce youth exposure. 30 In addition to public health and policy advocates, this study has implications for pediatric health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Although many factors are associated with tobacco use, research shows that exposure to, interest in, and positive attitudes about protobacco marketing and media messages are associated with increased odds of youth liking smoking, early initiation, and increased use. 7,8 This phenomenon seems to be global. Studies conducted around the world have found that youth with high exposure and awareness levels to protobacco messaging, whether through advertising, point-of-sale displays, depictions in movies, or promotional materials, are more likely to smoke.…”
mentioning
confidence: 99%
“…Several factors are involved in influencing youth to experiment with tobacco, including socioenvironmental (eg, advertising/media influences, peer influences, parental influences, ethnic and gender factors), psychological (eg, psychiatric illness or history, child development, weight concerns), and biological (eg, genetics) factors. 8,[30][31][32][33][34][35][36][37][38] Teenagers with at least 1 smoking parent are twice as likely to become smokers compared with teenagers whose parents do not smoke. 39 This is attributed to the availability of tobacco products in the home, modeling of the behavior, and the hypothesized role of nicotine receptor priming as a result of being exposed to nicotine in utero and secondhand smoke after birth.…”
Section: Initiation Of Tobacco Use and Onset Of Addictionmentioning
confidence: 99%
“…3 Depiction of smoking in movies has been a particularly pernicious influence. 5 Although most of the research on media influences has been conducted in a few high-income countries, distribution of free cigarettes and widespread awareness of tobacco advertisements has been demonstrated among children in Africa. 6,7 Tobacco consumption is a major cause of illness and death.…”
mentioning
confidence: 99%